Malaysian Investors' Knowledge Towards Unit Trust - Sim, Kar Yi (2008)
This study finds that knowledge level among the Malaysian investing public is at a low level. Malaysian investors are found to be investing in unit trusts without knowing that a unit trust is. They are found to have a wrong understanding towards certain basic concepts of unit trusts.